PENINGKATAN BELAJAR MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH PADA MAHASISWA POLITEKNIK TANJUNGBALAI (POLTAN)SUMATERA UTARA - Zulkhairani; Hidayatullah; Mhd.Ihsan (Smart Education, 2026)
This study was designed to improve student learning engagement using the Make a Match cooperative learning model for students at Tanjungbalai Polytechnic. The learning engagement in this study focused on physical and mental engagement. This study employed Classroom Action Research (CAR), where the lecturer acted as the learning implementer while the researcher acted as the observer. The design of the study employed the Kemmis and Mc. Taggart model. This study was conducted in the even semester. The subjects were students at Tanjungbalai Polytechnic. The object of the study was the participants' learning engagement, and data collection techniques used observation and interviews. The data were analyzed descriptively and presented in tables and graphs. The results showed an increase in student learning engagement in siklus I, reaching 80.10% (good category), and then in siklus II, increasing to 90.10% (very good category). This represents a 9.54% increase. Therefore, the use of the Make a Match cooperative learning model in courses at Tanjungbalai Polytechnic is